The Influence Of World Crude Oil Prices, Dow Jones Industrial Average And Inflation On Stock Price Index (Case Study of Companies Listed on the Indonesia Stock Exchange Energy Sector Period 2016-2022) - Prayogi, Dalih; Martaseli, Evi; Indrawan, Andri (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the Influence Of World Crude Oil Prices, Dow Jones Industrial Average And Inflation On Price Index Share In Companies Listed on the Indonesian Stock Exchange Energy Sector Period 2016-2022. Method The research used is a descriptive method. Sample in this study were selected using purposive sampling and obtained 12 companies with 7 years of observation and obtained 84 data. The results of this research partially show that Crude Oil has a significant positive effect on the Energy Sector Stock Price Index, Down Jones Industrial Average has an insignificant negative effect on the Price Index Energy Sector Shares, Inflation has a significant positive effect to the Energy Sector Stock Price Index. Meanwhile, simultaneously crude oil, down Jones industrial average and inflation together have a positive and insignificant effect on the Stock Price Index in the Energy Sector Stock Price Index.